Aplikasi Pemakaian Gedung Pendopo dan Peminjaman Peralatan Pada Bagian Umum Kantor Walikota Dumai Berbasis Web - Amat Sofiyan; Abdul Kohar; Deasy Wahyuni; Ahmedika Azkiya (JOSTECH Journal of Science and Technology, 2023)
Providing excellent public services is the goal of every local government. The Dumai City Government is currently competing to implement and take advantage of advances in information technology to help create effective public services. With the lack of efficiency in borrowing the pavilion building and equipment in the general section of the Dumai Mayor's office, still using letter requests is the cause of this problem. Therefore, making this web-based application called the application for the use of the Pendopo Building and borrowing equipment at the general part of the Dumai Mayor's office was carried out as an effort to overcome this problem. This application development is based on PHP programming. This application provides various kinds of facilities for borrowing the building and the equipment that is therein.